Strategi Mendorong Kinerja Pegawai dengan Meningkatkan Komunikasi Interpersonal dan Komitmen Organisasi - Conchita Valentina Latupapua (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
Interpersonal communication is a communication process that occurs between two or more people and occurs in direct reciprocity. Meanwhile, Organizational Commitment is the degree to which employees want to continue to actively participate in the organization. The purpose of this study was to determine all the effects of Interpersonal Communication and Organizational Commitment. This study explains the relationship between variables partially with the sampling method with the census method of 37 employees of the Maluku Province Agricultural and Animal Protection Center. The analysis method used is multiple linear regression analysis. From the results of this test, the influence of Interpersonal Communication (X1) and Organizational Commitment (X2) is obtained. The dependent variable is Employee Performance (Y). The results of this study indicate that the more both employees build and improve interpersonal communication and Organizational Commitment will improve employee performance.